2017
DOI: 10.1007/s40271-017-0226-z
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Up: How Patient and Physician Voices Shaped a Trial to Improve Goals-of-Care Discussions

Abstract: Stakeholder input informed the development of a novel intervention that physicians seemed to find both valuable and in sync with their needs and their practice schedules. Where communication about difficult subjects and shared decision making are involved, including multiple stakeholder groups in study design, implementation, and outcomes measurement may have far-reaching effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…[ 67 , 68 ], role description templates [ 68 ], structures for consensus decision making [ 69 ], and methods for reimbursement and compensation to patient partners [ 70 – 73 ]. Mutual respect was offered through documents summarizing the evidence to facilitate team discussions [ 74 ], through communications skills training modules [ 75 ], and through newsletter templates. Co-building was evidenced through partnership surveys [ 76 , 77 ] and documents that categorized various patient partner roles in governance, team meetings/working groups [ 74 , 78 ], workshops/conference attendance [ 74 ], authorship, and in identifying patient-reported outcomes (PROs) [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 67 , 68 ], role description templates [ 68 ], structures for consensus decision making [ 69 ], and methods for reimbursement and compensation to patient partners [ 70 – 73 ]. Mutual respect was offered through documents summarizing the evidence to facilitate team discussions [ 74 ], through communications skills training modules [ 75 ], and through newsletter templates. Co-building was evidenced through partnership surveys [ 76 , 77 ] and documents that categorized various patient partner roles in governance, team meetings/working groups [ 74 , 78 ], workshops/conference attendance [ 74 ], authorship, and in identifying patient-reported outcomes (PROs) [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data, as summarized in Table 1 , exhibit a range of pragmatic clinical trials conducted between 2004 and 2022, located primarily in the United States (three studies) and the United Kingdom (three studies), with one study in Denmark [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The trials involved patients with different cancer types, including breast (three studies), esophageal (one study), and high-grade non-muscle-invasive bladder cancer (one study); one study included multiple cancer types, namely breast, colorectal, and non-small cell lung [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data, as summarized in Table 1 , exhibit a range of pragmatic clinical trials conducted between 2004 and 2022, located primarily in the United States (three studies) and the United Kingdom (three studies), with one study in Denmark [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The trials involved patients with different cancer types, including breast (three studies), esophageal (one study), and high-grade non-muscle-invasive bladder cancer (one study); one study included multiple cancer types, namely breast, colorectal, and non-small cell lung [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The patient populations in these trials consisted of individuals at different cancer stages, including early stages (two studies), advanced stages (two studies), and mixed stages (one study), as well as cases where the stage was not specified (two studies) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, results from the Coping with Cancer study suggested that patients with such psychosocial factors as emotional numbness may have their fears rather exacerbated by end-of-life discussions, resulting in unreasonable demands of care and life-maintaining treatments [49]. Educational initiatives to improve communication and enhance implication in decision-making among seriously ill patients are therefore needed and are currently being developed in protocols interestingly involving both healthcarers and patients/caregivers perspectives [50][51][52]. Since this module provides additional information on patient preferences for anticipation, a theme that is not addressed by the API, and since it is well accepted by patients, our clinical vignette can be used in conjunction with the API, as a comprehensive scale to guide doctor-patient communication in the context of advanced cancer.…”
Section: Discussionmentioning
confidence: 99%